Impact of diagnosis‐to‐ablation time on non‐pulmonary vein triggers and ablation outcomes in persistent atrial fibrillation - Takamiya, Tomomasa; Nitta, Junichi; Inaba, Osamu; Sato, Akira; Inamura, Yukihiro; Murata, Kazuya; Ikenouchi, Takashi; Kono, Toshikazu; Takahashi, Yoshihide; Goya, Masahiko; Sasano, Tetsuo (Journal of cardiovascular electrophysiology, 2021)
Introduction Non‐pulmonary vein (PV) triggers are a major cause of atrial tachyarrhythmia (ATA) recurrence after catheter ablation. However, the effect of the diagnosis‐to‐ablation time (DAT) on non‐PV triggers in persistent atrial fibrillation is unknown. Methods and Results This observational study evaluated 502 consecutive persistent AF patients who underwent initial ablation. We compared 408 patients whose DAT was <3 years with 94 patients whose DAT was ≥3 years. Following PV and posterior wall isolation, 193 non‐PV triggers, including 50 AFs, 30 atrial tachycardias (ATs), and 113 repetitive atrial premature beats, were elicited and ablated in 137 (27%) patients. Specifically, 80 non‐PV AF/AT triggers were provoked in 64 (13%) patients, being identified more frequently in the DAT ≥ 3 years group than in the DAT < 3 years group (20% vs. 11%, p = .025) especially with a higher prevalence of coronary sinus/inferior left atrial triggers. During a median follow‐up of 770 days, the ATA recurrence‐free rate was higher in the DAT < 3 years group than the DAT ≥ 3 years group (79% vs. 53% at 2 years, p < .001). In a multivariate analysis, female sex (odds ratio: 2.70, p = .002) and a longer DAT (odds ratio: 1.13/year, p = .008) were predictors of non‐PV AF/AT triggers, and a longer DAT (hazard ratio: 1.12/year, p < .001) and non‐PV AT/AF triggers (hazard ratio: 1.79, p = .009) were associated with ATA recurrence. Conclusion Early ablation after the first diagnosis of persistent AF may reduce emerging non‐PV AF/AT triggers and ATA recurrence.